Adolescent mothers consuming alcohol and other drugs: a descriptive study (Research, Society and Development, 2020)
Objective: to analyze the sociodemographic, obstetric, and problematic use of alcohol and other drugs during pregnancy in adolescent mothers with a hospitalized child. Method: Descriptive quantitative research. Data collection took place in two neonatal intensive care units, in the state of Rio de Janeiro with the consultation of medical records. Simple descriptive statistical analysis was performed. Results: The 13 adolescents were aged 13 to 17 years (69.2%), single (92.3%), with incomplete elementary school (84.6%), family income of one and a half minimum wage (92.3%). The newborns with incomplete prenatal care (61.5%), preterm gestational age (69.2%) and term (30.8%). Vaginal delivery predominated (69.2%) and the babies were diagnosed with prevalent hospitalization prevalent for early respiratory distress (38.4%) and prematurity (38.4%). They started using drugs in the age group between 10 to 15 years old (61.5%), mainly used alcohol (92.3%), cigarettes (30.7%), marijuana (30.7%), and crack (15, 4%). Conclusion: Sociodemographic data showed a profile similar to that described in the literature. Adolescent mothers have characteristics that make them vulnerable on an individual and social level. They had problematic alcohol consumption (92.3%), cigarettes (30.7%), marijuana (30.7%) and crack (15.4%) during pregnancy. The newborn children are hospitalized for prematurity, early respiratory distress, congenital syphilis, hypoglycemia, low weight, neonatal asphyxia, sepsis and congenital heart disease. The importance of qualification and / or training of nurses and other health professionals is confirmed in welcoming this woman to prevent and detect the use of these substances, avoiding gestational comorbidities and child morbidity and mortality.